Use of physiological activities to estimate the population growth of rotifer (Brachionus calyciflorus) under the stress of toxic Microcystis and nitrite. (December 2021) - Liang, Ye; Zhou, Yang; Wang, Yishan; Liu, Rui; Qi, Jun; Lin, Yangjie; Zhang, Tongqing; Jiang, Qichen
Abstract: Microcystis blooms disrupt aquatic systems and adversely affect zooplankton growth. Brachionus calyciflorus Pallas (rotifer) was introduced to different combinations of toxic Microcystis aeruginosa (0, 2 × 10 5, 2 × 10 6, and 2 × 10 7 cells mL −1 ) and nitrite (0, 2, 4, and 6 mg L −1 ) to evaluate their physiological activities and population growth under stress. Survival rate ( S ), population growth rate ( r ), grazing rate ( G ), antioxidant response, and metabolic and digestive enzyme activities were determined. Results revealed that G declined with the increasing nitrite doses and grazing time upon exposure to a certain Microcystis concentration. Toxic M. aeruginosa and nitrite inhibited the S, r, glutathione content, total antioxidant capacity level, and activities of alkaline phosphatase, xanthine oxidase, lactate dehydrogenase, and cellulase ( p < 0.05) but increased the reactive oxygen species level, malondialdehyde content, and amylase activity ( p < 0.05). The activities of superoxide dismutase, catalase, and pepsase were also increased in single low doses of nitrite solutions ( p < 0.05). Therefore, the grazing intensity of rotifers affected B. calyciflorus physiological activities, which are useful in the estimation of its population growth in eutrophic water environments. Highlights: Microcystis and nitrite are harmful to the population growth of rotifers. Rotifers change their physiological activities in response to eutrophic conditions. Combined Microcystis and nitrite induces oxidative stress and lipid peroxidation. Physiological activities are useful in the estimation of rotifer population growth.